2011
DOI: 10.1089/cmb.2011.0128
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of the Gapped Consecutive-Ones Property Problem for Matrices of Bounded Maximum Degree

Abstract: The Gapped Consecutive-Ones Property (C1P) Problem, or the (k, δ)-C1P Problem is: given a binary matrix M and integers k and δ, decide if the columns of M can be ordered such that each row contains at most k blocks of 1's, and no two neighboring blocks of 1's are separated by a gap of more than δ 0's. This problem was introduced by Chauve et al. ( 2009b ). The classical polynomial-time solvable C1P Problem is equivalent to the (1, 0)-C1P problem. It has been shown that, for every unbounded or bounded k ≥ 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…So indeed, in this case, aside from the single open case of the complexity of the (2,1)-C1P, there is also a strict complexity border between the classical C1P ((1,0)-C1P in the gapped C1P context) and this relaxed model. In Maňuch and Patterson (2010), the authors show also for binary matrices of bounded degree d that the k-C1P is NP-complete even when d ¼ 3, which is quite suprising, as this is the weakest form of consecutivity requirement: in each row, only two of the ones must be adjacent. This is shown with an NPcompleteness construction based on finding a collection of walks on a hypergraph H that covers each hyperedge in H, a technique that inspired some of the NP-completeness constructions in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So indeed, in this case, aside from the single open case of the complexity of the (2,1)-C1P, there is also a strict complexity border between the classical C1P ((1,0)-C1P in the gapped C1P context) and this relaxed model. In Maňuch and Patterson (2010), the authors show also for binary matrices of bounded degree d that the k-C1P is NP-complete even when d ¼ 3, which is quite suprising, as this is the weakest form of consecutivity requirement: in each row, only two of the ones must be adjacent. This is shown with an NPcompleteness construction based on finding a collection of walks on a hypergraph H that covers each hyperedge in H, a technique that inspired some of the NP-completeness constructions in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The general technique of the reduction is similar to that used in Maňuch and Patterson (2010) to prove NPhardness for a generalized variant of the Consecutive Ones Problem. Please note that, in the rather abstract ambience of this proof, we will use the term object instead of gene.…”
mentioning
confidence: 99%
“…Further variations of consecutive-ones problems that could be interesting for linear diagrams have been studied, mostly giving hardness results or polynomial algorithms assuming that some underlying parameters of the problems are constant: It has been shown that the problem of finding a permutation π of the columns of a binary matrix A such that for all i ∈ [m A ], cons1(r A i ) ≤ k ∈ N is NP-complete [12], which translates to the problem of having at most k line segments per set in a linear diagram. Another more involved problem has been studied, called Gapped Consecutive Ones, in which we are given a binary matrix A and want to find a permutation π of the columns of A such that for all i ∈ [m A ], cons1(r A i ) ≤ k ∈ N, and the gaps between two consecutive blocks of ones in a row of π(A) is at most some maximum gap parameter δ [8,22,23].…”
Section: Consecutive Block Minimizationmentioning
confidence: 99%
“…In the absence of a good model for genome structural evolution, mapping techniques for ancestral genomes, introduced by Bergeron et al (2004 ), have given the most reliable ancestral configurations on animals ( Chauve and Tannier, 2008 ; Ma et al , 2006 ; Ouangraoua et al , 2009 ), yeast ( Bertrand et al , 2010 ; Chauve et al , 2010a ; Tannier, 2009 ), or plant genomes ( Murat et al , 2010 ), and even on a wide eukaryote dataset ( Muffato, 2010 ; Muffato et al , 2010 ). These works also raised new methodological issues and stimulated a recent stream of algorithmic studies related to genome mapping ( Adam et al , 2007 ; Chauve et al , 2010b Chauve et al , 2009 ; Dom, 2009 ; Dom et al , 2010 ; Manuch and Patterson, 2010 ; Stoye and Wittler, 2009 ; Wittler and Stoye, 2010 ;), which had taken the back seat with the development of massive genome sequencing.…”
Section: Introductionmentioning
confidence: 99%